Erosive tooth wear inhibition by hybrid coatings with encapsulated fluoride and stannous ions - Bezerra, Sávio José Cardoso; Viana, Ítallo Emídio Lira; Aoki, Idalina Vieira; Sobral, Maria Angela Pita; Borges, Alessandra Buhler [UNESP]; Hara, Anderson T.; Scaramucci, Taís (Springer Nature, 2021)
This study aimed to formulate a hybrid coating material (HC) and to modify this HC with fluoride (NaF) and stannous (SnCl2) ions, directly or encapsulated in nano containers, testing the effects of these materials against dental erosion and erosion–abrasion. Enamel and dentin specimens were treated with the HCs, and then tested in erosion or erosion–abrasion cycling models of 5 days (n = 10 for each substrate, for each model). Deionized water was the negative control, and a fluoride varnish, the positive control. Surface loss (SL, in µm) was evaluated with an optical profilometer, and data were statistically analyzed (α = 0.05). For enamel, in erosion, the positive control and HC without additives showed significantly lower SL than the negative control (p = 0.003 and p = 0.001). In erosion–abrasion, none of the groups differed from the negative control (p > 0.05). For dentin, in erosion, the positive control, HC without additives, HC with non-encapsulated F, and HC with encapsulated F + Sn showed lower SL than the negative control (p < 0.05). In erosion–abrasion, none of the groups differed significantly from the negative control (p < 0.05). HC without additives showed a promising potential for protecting the teeth against dental erosion (with upward trend for improved protection on dentin), but not against erosion–abrasion. The presence of additives did not improve the protective effect of the HC, on both substrates. [Figure not available: see fulltext.]